Promoting Menstrual Hygiene Management Education for Adolescent Girls: A Community Service Initiative: Promosi Menstrual Hygiene Management pada Remaja Putri: Sebuah Inisiatif Pengabdian Masyarakat - Hadina, Hadina; Batjo, Siti Hadijah; Hadriani, Hadriani (Jurnal Pengabdian Bidan Nasuha, 2023)
Introduction: Menstrual hygiene management (MHM) is an important part of menstruation to maintain the health and dignity of women and adolescent girls. Purpose: The purpose of this community service is to provide education about menstrual hygiene management (MHM) to adolescent girls. Methods: This activity was carried out on 20-24 May 2022 at MTS Salabangka, Paku Bungku Selatan village, the working area of the Kaleroang puskesmas, kec. Bungku Selatan Kab. Morowali. The target audience of this activity is all students of class VII and VIII MTs Salabangka. This community service was carried out by providing education through leaflet media, demonstrations, lectures and questions and answers. Results: The pretest results on adolescent girls in South Bungku found 66.6% who had poor knowledge and there were 33.4% who had good knowledge about menstrual hygiene management. In addition, only 6% were found to wash sanitary napkins before disposal. The post test results still showed 23.8% participants with poor knowledge and 76.3% participants with good knowledge. Conclusion: Menstrual hygiene management (MHM) education is very important, especially for adolescent girls less than 15 years old by parents, teachers and health workers. Facilities in schools, especially sanitary napkins, water, separate washing toilets for boys and girls need attention from the school.